2012
DOI: 10.1517/14656566.2012.730041
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan succinate: pharmacokinetics of different formulations in clinical practice

Abstract: Subcutaneous sumatriptan has been considered as the most efficacious treatment in the acute phase of migraine both on pain alone as well as on associated autonomic symptoms. Pharmacologically, pharmacokinetic parameters, in particular bioavailability, T(max) and C(max) are responsible for the wide efficacy of the compound and the limited adverse effect (AE) profile. The new drug formulations that are the most similar to the pharmacokinetics parameters of the subcutaneous one are promising because they both imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…Absorption was substantially faster than for orally administered zolmitriptan, with less measurable N-desmethyl zolmitriptan metabolite, presumably due to a lack of first pass metabolism. PK parameters for subcutaneous sumatriptan and oral zolmitritpan in this study were similar to those previously reported [14,15].…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Absorption was substantially faster than for orally administered zolmitriptan, with less measurable N-desmethyl zolmitriptan metabolite, presumably due to a lack of first pass metabolism. PK parameters for subcutaneous sumatriptan and oral zolmitritpan in this study were similar to those previously reported [14,15].…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…5-Hydroxytryptamine-1 receptor agonists (triptans) are the preferred first-line treatment for patients with no contraindications and have moderate to severe migraine [19]. Sumatriptan succinate is the first "triptan" drug which has been identified to have a substantial effect on the treatment of acute migraine and cluster headache.…”
Section: Sumatriptan Succinatementioning
confidence: 99%
“…Neurological aura symptoms are also observed in some patients. 1,2 Nonspecific treatments such as antiemetics are prescribed in treating any kind of pain, and specific therapies such as triptans are exclusively effective in treating migraine and related disorders. 3,4 Triptans are frequently prescribed in the treatment of acute migraine attacks as they are potent in providing wide efficacy and tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Triptans are frequently prescribed in the treatment of acute migraine attacks as they are potent in providing wide efficacy and tolerability. 1,5 Sumatriptan succinate (Sum) as a 5-HT1receptor agonist is employed in the removal of symptoms of migraine headaches. However, due to severe nausea or vomiting during the migraine attacks and low oral bioavailability (15%) because of high first-pass metabolism, the oral treatment proves unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%